The Influence of the Smart Indonesia Program (PIP) on Student Learning Motivation at SMP Negeri 1 Dolok Merawan, Dolok Merawan District, Serdang Bedagai Regency, Academic Year 2021/2022 - Perangin-angin, Fitria Geasani; Siregar, Chairuddin; Siregar, Abdul Rosip (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2023)
The purpose of this study was to determine the Learning Motivation of Students who received the Smart Indonesia Program (PIP) at SMP Negeri 1 Dolok Merawan and the Effect of the Smart Indonesia Program (PIP) on Student Motivation at SMP Negeri 1 Dolok Merawan. This research uses quantitative methods. The results of this study, the learning motivation of students at SMP Negeri 1 Dolok Merawan is quite high, the relationship obtained through the Product Moment correlation test between the influence of the Smart Indonesia Program (PIP) and the learning motivation of students at SMP Negeri 1 Dolok Merawan has a positive correlation or a positive correlation. walk in the same direction. Through the Product Moment table r value can be interpreted at a significant level of 0.297. By comparing the magnitude of rcount with rtable, it can be seen that the value of rcount > rtable is 0.4577 > 0.297. Thus the hypothesis taken is Ha, which means that there is a significant influence between the learning motivation of students who receive assistance from the Smart Indonesia Program (PIP) at SMP Negeri 1 Dolok Merawan Academic Year 2021/2022. Based on the calculation of the Determinant Coefficient, it can be seen that the influence value of the Smart Indonesia Program (PIP) on student learning motivation at Dolok Merawan 1 Public Middle School is 21%, this means that the variation in student learning motivation at Dolok Merawan 1 Public Middle School is due to the Smart Indonesia Program (PIP) ), while the remaining 79% is caused by other variables not included in this study